Nitric oxide synthase (nNOS) gene transfer modifies venous bypass graft remodeling: effects on vascular smooth muscle cell differentiation and superoxide production. - West, N; Qian, H; Guzik, T; Black, E; Cai, S; George, SE; Channon, K (2001)
BACKGROUND: Pathological vascular remodeling in venous bypass grafts (VGs) results in smooth muscle cell (SMC) intimal hyperplasia and provides the substrate for progressive atherosclerosis, the principal cause of late VG failure. Nitric oxide (NO) bioactivity is reduced in VGs, in association with increased vascular superoxide production, but how these features relate to pathological VG remodeling remains unclear. We used gene transfer of the neuronal isoform of nitric oxide synthase (nNOS) to investigate how increased NO production modulates vascular remodeling in VGs and determined the effects on late VG phenotype. METHODS AND RESULTS: New Zealand White rabbits (n=60) underwent jugular-carotid interposition bypass graft surgery with intraoperative adenoviral gene transfer of nNOS or beta-galactosidase. Vessels were analyzed after 3 days (early, to investigate acute injury/inflammation) or 28 days (late, to investigate SMC intimal hyperplasia). In early VGs, nNOS gene transfer significantly increased NOS activity and substantially reduced adhesion molecule expression and inflammatory cell infiltration. In late VGs, recombinant nNOS protein was no longer evident, but there were sustained effects on VG remodeling, resulting in a striking reduction in SMC intimal hyperplasia, a more differentiated intimal SMC phenotype, and reduced vascular superoxide production. CONCLUSIONS: Intraoperative nNOS gene transfer has sustained favorable effects on VG remodeling and on the vascular phenotype of mature VGs. These findings suggest that early, transient modification of the response to vascular injury is a powerful approach to modulate VG biology and highlight the potential utility of NOS gene transfer as a therapeutic strategy in VGs.